The effect of combination of triamcinolone acetonide and methotrexate on keloidfibroblast activity in dermis equivalent - Endra Yustin E. S; Fajar Waskito; Yohanes Widodo Wirohadidjojo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Triamcinolone acetonid (TA) intralesion has been a standard treatment for keloids for manyyears, due to its effect in inhibiting collagen synthesis and fibroblast proliferation. However, until now theclinical result is unsatisfactory. Keloid flattening is slow and sometimes adverse reactions may occur.Methotrexate (MTX) is a chemotherapeutic agent having an antiproliferating effect which act as an antifolicacid. Because of this effect, MTX is potential to be used in combination with TA for the treatment inkeloid. Fibroblast populated collagen lattice (FPCL) was a dermal equivalent usually used for fibroblastactivity measurement.Objective: To understand the inhibition of fibroblast keloid activities of MTX in vitro on FPCL contraction,compared to TA and MTX plus TA.Methods: This research used simple parallel multigroups experimental study design, and conducted on thirdpassage keloid fibroblast culture, which was isolated from one patient. Fibroblast was cultivated in collagentype 1 from rat tail (FPCL). Keloid fibroblasts was classified into 16 groups, and treated with 5, 10, 20mM TA, 1.75, 3.5, 7 mM MTX, combination of TA and MTX, and a control negative. FPCL contractionindicating activities of fibroblast was measured using Scion Image software. Mean of FPCL contractionwas analyzed using one way analysis of variance (ANOVA).Results: All treatments could inhibit FPCL contraction until day 2 (p<0.05). The highest inhibition of FPCLwas found in combination of TA 20 mM + MTX 7 mM (p<0.05). The treatment that could inhibit FPCLcontraction until day 3 was only group MTX 3.5 mM + TA 20 mM. This result indicated that a combinationof TA and MTX was stronger in inhibiting keloid fibroblast activities compared with TA and MTX alone.Key words: keloid fibroblast - growth factors - triamcinolone acetonid - methotrexate - FPCL contraction